2021
DOI: 10.3390/ijms222111441
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1-Associated Pathological Processes: Inhibition by Natural Polyphenols

Abstract: Poly (ADP-ribose) polymerase-1 (PARP-1) is a nuclear enzyme involved in processes of cell cycle regulation, DNA repair, transcription, and replication. Hyperactivity of PARP-1 induced by changes in cell homeostasis promotes development of chronic pathological processes leading to cell death during various metabolic disorders, cardiovascular and neurodegenerative diseases. In contrast, tumor growth is accompanied by a moderate activation of PARP-1 that supports survival of tumor cells due to enhancement of DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 156 publications
(155 reference statements)
1
13
0
Order By: Relevance
“…As expected, during transcription of the nucleosomal templates in the absence of PARP1, characteristic pauses were observed at the positions + (11)(12)(13)(14)(15), + (26)(27), + (35)(36)(37) and + (45)(46)(47)(48) bp from the promoter-proximal nucleosome boundary (Figure 1b) [28]. Transcription in the presence of non-PARylated PARP1 (in the absence of NAD+) results in a moderate decrease in the overall efficiency of nucleosome traversal by yPol II and an increase of pausing at positions + (28)(29) and +(38-40) (Figure 1b).…”
Section: Parp1 Facilitates Transcription Through the Nucleosome By Po...supporting
confidence: 81%
See 1 more Smart Citation
“…As expected, during transcription of the nucleosomal templates in the absence of PARP1, characteristic pauses were observed at the positions + (11)(12)(13)(14)(15), + (26)(27), + (35)(36)(37) and + (45)(46)(47)(48) bp from the promoter-proximal nucleosome boundary (Figure 1b) [28]. Transcription in the presence of non-PARylated PARP1 (in the absence of NAD+) results in a moderate decrease in the overall efficiency of nucleosome traversal by yPol II and an increase of pausing at positions + (28)(29) and +(38-40) (Figure 1b).…”
Section: Parp1 Facilitates Transcription Through the Nucleosome By Po...supporting
confidence: 81%
“…Core histones [9] and linker histone H1 [10] are among the targets for PARylation. Some inhibitors of PARP1 enzymatic activity are important anticancer compounds [11,12]. In particular, inhibition of PARP1 by olaparib induces synthetic lethality in tumor cells deficient in enzymes involved in homologous recombination DNA repair [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The information can be used for in-depth study. In recent years, poly (ADP-ribose) polymerase (PARP) inhibitor has been considered a promising anti-tumor drug ( 53 ). The combination of PARP inhibitor and chemotherapeutic agents is expected to overcome the drug resistance of tumor cells ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, poly (ADP-ribose) polymerase (PARP) inhibitor has been considered a promising anti-tumor drug ( 53 ). The combination of PARP inhibitor and chemotherapeutic agents is expected to overcome the drug resistance of tumor cells ( 53 ). A study reported that the combined use of MSLN-TTC (Targeted 227Th conjugate, radiopharmaceuticals) and PARP inhibitor may be a novel strategy for the treatment of MSLN -positive ovarian cancer ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…The catalytic activityindependent function is realized during interaction of PARP-1 with intractable chromatin regions where it makes protein-binding sites on DNA available for interactions with pioneer factors [2]. Impaired PARP-1 metabolism is associated with the development of various cancers, as well as cardiovascular and neurodegenerative diseases [5]. Accordingly, PARP-1 inhibitors are used as antitumor drugs, and the applicability to the treatment of other metabolic diseases is being investigated [6].…”
mentioning
confidence: 99%